Intercalations and Characterization of Zinc/Aluminium Layered Double Hydroxide-Cinnamic Acid - Nurain Adam; Sheikh Ahmad Izaddin Sheikh Mohd Ghazali; Nur Nadia Dzulkifli; Cik Rohaida Che Hak; Siti Halimah Sarijo (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
Cinnamic acid (CA) is known to lose its definite function by forming into radicals that able to penetrate into the skin and lead to health issues. Incorporating CA into zinc/aluminum-layered double hydroxides (Zn/Al-LDH) able to reduce photodegradation and eliminate close contact between skin and CA. Co-precipitation or direct method used by using zinc nitrate hexahydrate and aluminium nitrate nonahydrate as starting precursors with addition of various concentration of CA. The pH were kept constant at 7 ± 0.5. Fourier Transform Infrared-Attenuated Total Reflectance (FTIR-ATR) shows the presence of nanocomposites peak 3381 cm–1 for OH group, 1641 cm–1 for C=O group, 1543 cm–1 for C=C group and 1206 cm–1 for C–O group  and disappearance of  N–O peak at 1352 cm–1 indicates that cinnamic acid were intercalated in between the layered structures. Powder X-Ray Diffraction (PXRD) analysis for Zn/Al-LDH show the basal spacing of 9.0 Ǻ indicates the presence of nitrate and increases to 18.0 Ǻ in basal spacing in 0.4M Zn/Al-LDH-CA. CHNS analysis stated that 40 % of cinnamic acid were being found and intercalated in between the interlayer region of the Zn/Al-LDH with higher thermal stability. Field Emission Scanning Electron Microscope (FESEM) images of 0.4 M Zn/Al-LDH-CA shows that the nanocomposites are in more compact, flaky non porous, large agglomerates with smooth the surfaces of the intercalated compound. Controlled release was successful with 80 % release in phosphite anion and 70 % release carbonate anion. The cinnamic acid was successfully inserted between the interlayer regions of Zn/Al-LDH with slow release formulation.